Dimensi Kemanusiaan dalam Sistem Ekonomi Islam (Sebuah Kajian dengan Pendekatan Filsafat Hukum Islam) - Rosyid, Maskur (Khazanah: Jurnal Studi Islam dan Humaniora, 2015)
AbstractIslam has provided an economical system which certainly reflects the utiliza- tion of resources given by Allah to fulfill humans principal needs and give them good life. Moreover, Islamic economical system is not only based on divinity and moral values, but also based on humanism principal. This be- comes the antithesis of the capitalism system which had been practiced all these times which forced human to be a hedonistic, secularist, and materialistic economy doer. Through the pattern of Islamic philosophical law, the prob- lems will be analyzed by thinking comprehensively, radically, and reflective- critically.Key word: Humanism Dimension, Humanism, Islamic Economical System, Capitalist Economical System